Hukum kepegawaian. Mengenani kedudukan hak dan kewajiban pegawai negeri sipil. - TRIATMOJO, Sudibyo (Ghalia Indonesia, 1983)
Hukum kepegawaian. Mengenai kedudukan hak dan kewajiban pegawai negeri sipil